2007
DOI: 10.1562/0031-8655(2003)0780349pdfaod2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Dimer Formation and Oxidative Damage in M13 Bacteriophage Inactivation by Ultraviolet C Irradiation¶

Abstract: The mechanism by which UV‐C irradiation inactivates M13 bacteriophage was studied by analyzing the M13 genome using agarose gel electrophoresis and South‐Western blotting for pyrimidine dimers. The involvement of singlet oxygen (1O2) was also investigated using azide and deuterium oxide and under deoxygenated conditions. With a decrease in M13 infectivity on irradiation, single‐stranded circular genomic DNA (sc‐DNA) was converted to Form I and Form II, which had an electrophoretic mobility between that of sc‐D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…For the phage particle to be able to replication, the phage DNA must be capable to replicate in the host bacteria, as previously been shown by phage inactivation by UV irradiation [14] Fig. S1, and in the cartoon in Fig.S2.…”
Section: Designing the Methodsmentioning
confidence: 64%
“…For the phage particle to be able to replication, the phage DNA must be capable to replicate in the host bacteria, as previously been shown by phage inactivation by UV irradiation [14] Fig. S1, and in the cartoon in Fig.S2.…”
Section: Designing the Methodsmentioning
confidence: 64%
“…This is supported by the work of Napolitano et al, who suggested that inactivation should be due to protein damage, as ClO 2 reacts more readily with amino acids than with nucleotides (11). UV is often reported to cause fatal genome damage by forming pyrimidine dimers (4,12,13), and yet protein damage has also been reported (14,15). Singlet oxygen has been found to cause protein crosslinking (16), whereas other studies report genome damage as the main target for disinfection (17,18).…”
mentioning
confidence: 91%
“…We monitored genome degradation using reverse transcription (RT)-PCR, because with this technique the viral genome must undergo enzymatic transcription before detection. For the considered viruses, detection of viral RNA would thus decline with increasing fluence whatever the targeted fragment, a rationale previously used for DNA of irradiated phage M13 (16). Hence, the decrease of viral infectivity due to UV was monitored simultaneously with the effect of UV radiation on nucleic acids.…”
mentioning
confidence: 99%